ANALISIS PERENCANAAN PEMBANGUNAN EKONOMI DAERAH NUSA TENGGARA TIMUR DALAM MENINGKATKAN PERTUMBUHAN EKONOMI - Firsa Asha Sabitha (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
East Nusa Tenggara is one of the regions in Indonesia whose economic level is still low, so a long-term and short-term economic plan is needed in increasing or increasing the economic growth rate of the NTT region. In planning the long-term economic development process of the NTT region, the government has several designs in increasing the economic growth of the NTT region, namely first, the government will accelerate the process of developing human resources in NTT through education. Second, there is infrastructure development and improvement in the NTT area. Third, NTT is known as an island that has beauty on its beaches. With the construction of infrastructure in the form of roads and bridges, it can facilitate travel access for local tourists and foreign tourists or tourists who will vacation on the coast of NTT island. The analytical methods and techniques that will be applied in this observation are qualitative analysis methods and techniques. Based on the DLQ calculations in the table above, it shows that the most superior sector in 2020 is the mining sector. The mining sector in 2020 to 2022 today, the mining sector has become the heart of the economic growth of eastern Indonesia. This is because the biggest potential of the eastern region is in the mining sector and has been supported by export activities on mining products in the eastern region.